THE NIGERIAN FEDERATION AND RESTRUCTURING DEBATE: IMPLICATIONS FOR SOCIO-POLITICAL AND ECONOMIC ADVANCEMENT - OKEREKA, Onofere Princewill; ORHERO, Abraham Ejogba; OLUKA, Nduka Lucas (EBSU Journal of Social Sciences and Humanities, 2022)
No issue in the contemporary Nigeria has commanded a greater concern and consensus than the clamour for restructuring and true-federation in recent time. In the face of the deepening crisis of ethnic agitations, political marginalization, secession movements, socio-economic failures, and the changing pattern of Nigeria’s national security challenges, there is a step-up in the clamour for fiscal federalism. Within this premise, this study made concerted effort to examine the political and economic experiences. Its specific objectives lie in its modest effort to examine the practice of the Nigeria’s federalism often dominated by the reasons, benefits and challenges of restructuring debates. To achieve its objective, historical research design was adopted, gleaned extant literature to enable us articulate the trajectory of the Nigeria political history. This implies that secondary sources of data were extensively deployed to elicit data for the study. This discourse finds it appropriate to adopt Structural functionalism as its theoretical framework base on its utility of being able to ensure that the Nigerian federalism is constitutionally restructured in such a manner that they can perform their appropriate functions that will enable the country achieve its desired political and economic development. The study amongst others revealed that the deepening crises of insecurity and secessionist movements are targeted at the installation of true- federalism. In order to resolve these revolving national issues, valid recommendations are made.The study suggests among others restructuring which in turn targets fiscal federalism which would automatically decentralised powers of the central government.